Tourism sector in Panama: Regional economic impacts and the potential to benefit the poor - Klytchnikova, Irina; Dorosh, Paul A. (Wiley, 2013)
Tourism is one of Latin America's fastest growing industries, but the impact of tourism on the poor and the effects on developing regions are under debate. Many studies have evaluated the growth impacts of the tourism sector but few have analyzed the impact of tourism on the economy and poverty at the subnational level in developing countries. This paper presents the results of a top‐down assessment of the impact of tourism spending on growth and poverty at the regional level in Panama using a Social Accounting Matrix multiplier model. As revealed by this study, the tourism sector has large multiplier effects on the Panamanian economy — higher than the Panama Canal and almost twice as high as the textiles sector or Free Zone of Colon — and has the potential for significant benefits to the poor, but these benefits depend on where and how supply chains are structured and on the way tourists spend their money.